Analisis Kelelahan Kerja Menggunakan Fatigue Assessment Scale pada PT. Indonesia Power Priok POMU - Lestari, Ika Dwiyana; Chirzun, Ahmad; Nurhasanah, Nunung (Metris: Jurnal Sains dan Teknologi, 2022)
Work fatigue is an important problem that must be handled properly because it can cause various problems, as fatigue is a major cause of work-related injuries and impacts productivity. Measure the level of fatigue of these workers will be carried out using the Fatigue Assessment Scale (FAS), a subjective fatigue measurement tool based on a questionnaire that is most appropriate for measuring the level of fatigue in workers. FAS has been rated as very reliable for measuring worker fatigue. The FAS consists of 10 questions examining physical and mental fatigue and their impact on activity motivation. If fatigue is not paid attention to, it will have an impact not only on the company but also on the workers themselves, ranging from causing work accidents to illnesses. Based on the calculations that have been done for the average answer to the Fatigue Assessment Scale (FAS) questionnaire, in this case, the highest average holder has represented physical and mental fatigue, number 4 represents physical fatigue, and number 10 represents mental fatigue. and based on the calculation results in the Likert scale, which gets an index of 97.7%, this indicates that for the level of fatigue itself, PT. Indonesia Power Priok POMU can be categorized as Very Good. Do not experience excessive work fatigue, and the workload does not exceed the workers' capabilities